Lysophosphatidic acid induces vasodilation mediated by LPA1 receptors, phospholipase C, and endothelial nitric oxide synthase. Issue 2 (18th November 2013) - Ruisanchez, Éva; Dancs, Péter; Kerék, Margit; Németh, Tamás; Faragó, Bernadett; Balogh, Andrea; Patil, Renukadevi; Jennings, Brett L.; Liliom, Károly; Malik, Kafait U.; Smrcka, Alan V.; Tigyi, Gabor; et al.
Abstract : Lysophosphatidic acid (LPA) has been implicated as a mediator of several cardiovascular functions, but its potential involvement in the control of vascular tone is obscure. Here, we show that both LPA (18:1) and VPC31143 (a synthetic agonist of LPA1–3 receptors) relax intact mouse thoracic aorta with similar Emax values (53.9 and 51.9% of phenylephrine‐induced precontraction), although the EC50 of LPA‐ and VPC31143‐induced vasorelaxations were different (400 vs. 15 nM, respectively). Mechanical removal of the endothelium or genetic deletion of endothelial nitric oxide synthase (eNOS) not only diminished vasorelaxation by LPA or VPC31143 but converted it to vasoconstriction. Freshly isolated mouse aortic endothelial cells expressed LPA1, LPA2, LPA4 and LPA5 transcripts. The LPA1–3 antagonist Ki16425, the LPA1 antagonist AM095, and the genetic deletion of LPA1, but not that of LPA2, abolished LPA‐induced vasorelaxation. Inhibition of the phosphoinositide 3 kinase‐protein kinase B/Akt pathway by wortmannin or MK‐2206 failed to influence the effect of LPA. However, pharmacological inhibition of phospholipase C (PLC) by U73122 or edelfosine, but not genetic deletion of PLCε, abolished LPA‐induced vasorelaxation and indicated that a PLC enzyme, other than PLCε, mediates the response. In summary, the present study identifies LPA as an endothelium‐dependent vasodilator substance acting via LPA1, PLC, and eNOS.—Ruisanchez, É., Dancs, P., Kerék, M., Németh, T., Faragó, B., Balogh, A., Patil, R., Jennings, B. L., Liliom, K., Malik, K. U., Smrcka, A. V., Tigyi, G., Benyó, Z. Lysophosphatidic acid induces vasodilation mediated by LPA1 receptors, phospholipase C, and endothelial nitric oxide synthase. FASEB J. 28, 880–890 (2014). www.fasebj.org